Pengaruh Pengaruh Perbedaan Asal Bibit Terhadap Respon Hasil dan Fisiologi Pada Tanaman Lidah Buaya Berumur 10 Bulan pada Lahan Pasir Pantai : Asal penangkar, Lidah buaya, Lahan pasir pantai. - Peny; Lunnadiyah Aprilia , Rennanti (innofarm, 2025)
Aloe vera (Aloe vera L.) is a horticultural plant with extensive benefits in health, cosmetics, and food industries. However, the decreasing harvest area and productivity of Aloe vera in Indonesia present challenges, making the extensification of marginal lands, such as coastal sandy soils, a viable alternative. The aims to evaluate the effect of seedling origins on the yield and physiological responses of 10-month-old Aloe vera plants grown on coastal sandy soils. The research was conducted in Tegalretno Village, Kebumen, using a Completely Randomized Block Design with a non-factorial arrangement. Five treatments based on seedling origins (Gunung Kidul, Bantul, Purbalingga, Cilacap, Kebumen) were tested with five replications. Observed parameters included yield (fresh and dry weight of plants and leaves, and leaf area) and physiology (stomatal density and RGR). The results showed that seedlings from Gunung Kidul (P1) produced significantly higher yields, including fresh weight (2,028.6 g), dry weight (68.14 g), and dry leaf weight (47.08 g). Although stomatal density (13.84–18.87 stomata/mm²) and RGR (0.27–0.35) were not statistically different among treatments, P1 exhibited the best overall performance. Seedlings from Gunung Kidul demonstrated superior adaptation to marginal coastal sandy soils and are recommended for improving Aloe vera productivity in similar areas.